Effectiveness of Structured Teaching Programme on Knowledge regarding Menstrual Hygiene among Adolescent Girls - Nidhi Maurya; Rina Bhowal; Komala Sesha Kumar (Chakra Brahmanda Lentera Institute, 2022)
Background: Menstruation is monthly uterine bleeding for 4-5 days, regularly coming every 28 days from puberty till menopause in a woman’s reproductive life. This study intended to assess the knowledge of adolescent girls regarding menstrual hygiene in selected senior secondary schools with the implementation of the structured teaching program. The study was conducted to assess the pre and post-interventional level of knowledge, evaluate the effectiveness of structured teaching programs, and determine the association between the levels of knowledge with selected demographic variables. Method: Using a quantitative research approach. The study used a pre-experimental one-group pre and post-test design. Sixty samples were selected by using a non-probability simple random sampling technique. The Variable was adolescent girls regarding menstrual hygiene and knowledge. Result: The results showed that in the overall knowledge level of adolescent girls regarding menstrual hygiene, in pre-test there were 37 number (61.67%) adolescent girls with inadequate knowledge, 23 number (38.33%) of adolescent girls with a moderate level of knowledge, whereas in posttest 21 number (35%) of adolescent girls had moderate knowledge, 39 numbers (65%) had adequate knowledge regarding menstrual hygiene. The posttest knowledge mean percentage was found higher (knowledge mean percentage was 76.12% with SD of 1.57 when compared with pre-test mean percentage knowledge mean percentage which was 52.04% with SD of 3.07). Conclusion: Knowledge mean percentage enhancement was 24.08%. The statistical paired ‘t’ test implies that the difference in the pre-test and posttest value was found statistically significant at 5% level (p<0.05) with a paired ‘t’ test value of 14.27. The study's overall findings showed that the structured teaching programme significantly improved adolescent girls' knowledge score regarding menstrual hygiene.